Harnessing Natural Killer Cells in Non-small Cell Lung Cancer - Conroy, Melissa; Barr, Martin (My University, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide. There are two main subtypes: small cell lung cancer (SCLC), and non-small cell lung cancer (NSCLC). NSCLC accounts for 85% of lung cancer diagnoses. Early lung cancer very often has no specific symptoms, and many patients present with late stage disease. Despite the various treatments currently available, many patients experience tumor relapse or develop therapeutic resistance, highlighting the need for more effective therapies. The development of immunotherapies has revolutionized the cancer treatment landscape by enhancing the body's own immune system to fight cancer. Natural killer (NK) cells are crucial anti-tumor immune cells, and their exclusion from the tumor microenvironment is associated with poorer survival. It is well established that NK cell frequencies and functions are impaired in NSCLC; thus, placing NK cell-based immunotherapies as a desirable therapeutic concept for this malignancy. Immunotherapies such as checkpoint inhibitors are transforming outcomes for NSCLC. This review explores the current treatment landscape for NSCLC, the role of NK cells and their dysfunction in the cancer setting, the advancement of NK cell therapies, and their future utility in NSCLC.
PUBLISHED
Keywords: NK cell therapies; NK cells; NSCLC; cancer; immunotherapy; Lung Cancer; Tumour immunology and immunotherapy